2023
DOI: 10.3390/su15065567
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic-Induced Calcite Precipitation (EICP) Method for Improving Hydraulic Erosion Resistance of Surface Sand Layer: A Laboratory Investigation

Abstract: As a bio-inspired calcite precipitation method, bio-grouting via enzymatic-induced calcite precipitation (EICP) uses free urease enzyme to catalyze the urea hydrolysis reaction. This soil stabilization approach is relatively new and insufficiently investigated, especially for applications involving surface layer stabilization of sandy soil deposits for increasing hydraulic erosion resistance. This paper presents a laboratory investigation on the surface erosion resistance improvements for compacted medium-grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…The test results show that, compared with traditional two-phase EICP treatment methods, the single-phase low pH method significantly improves the calcium conversion efficiency and the homogeneity of the calcium carbonate dispersion in these sand samples. Zomorodian et al [ 21 ] investigated the resistance to surface erosion of compressed medium-grade silica sand samples treated by different EICP methods. They found that, compared with the untreated sand, all EICP treatment methods significantly increase the erosion resistance of treated sand, and 1.0 M cementing solution is a more feasible option to achieve the optimal erosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The test results show that, compared with traditional two-phase EICP treatment methods, the single-phase low pH method significantly improves the calcium conversion efficiency and the homogeneity of the calcium carbonate dispersion in these sand samples. Zomorodian et al [ 21 ] investigated the resistance to surface erosion of compressed medium-grade silica sand samples treated by different EICP methods. They found that, compared with the untreated sand, all EICP treatment methods significantly increase the erosion resistance of treated sand, and 1.0 M cementing solution is a more feasible option to achieve the optimal erosion resistance.…”
Section: Introductionmentioning
confidence: 99%